2002
DOI: 10.1063/1.1481786
|View full text |Cite|
|
Sign up to set email alerts
|

Strain and composition distributions in wurtzite InGaN/GaN layers extracted from x-ray reciprocal space mapping

Abstract: Strain and composition distributions within wurtzite InGaN/GaN layers are investigated by high-resolution reciprocal space mapping (RSM). We illustrate the potential of RSM to detect composition and strain gradients independently. This information is extracted from the elongation of broadened reciprocal lattice points (RLP) in asymmetric x-ray reflections. Three InxGa12xN/GaN (nominal x50.25) samples with layer thickness of 60, 120, and 240 nm, were grown in a commercial metal-organic chemical vapor deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(159 citation statements)
references
References 15 publications
6
152
1
Order By: Relevance
“…However, the RSMs did not allow us to discern between composition and strain gradients, as performed for instance in Ref. 29. Nevertheless, the broadening of the x-ray peaks in Fig.…”
Section: Sample In Content (X)mentioning
confidence: 92%
See 1 more Smart Citation
“…However, the RSMs did not allow us to discern between composition and strain gradients, as performed for instance in Ref. 29. Nevertheless, the broadening of the x-ray peaks in Fig.…”
Section: Sample In Content (X)mentioning
confidence: 92%
“…13,19 The presence of in-depth strain and composition gradients in the InGaN alloy seems to depend on the particular growth method and growth conditions. For instance, Pereira et al 29 showed that the relaxation of strain in InGaN epilayers grown by metal organic chemical vapor deposition (MOCVD) is accompanied by increased In contents. Similarly, Wang et al 41 reported increased In contents along the growth direction in Ga-rich InGaN layers grown by MOCVD.…”
Section: -5mentioning
confidence: 99%
“…This effect became more pronounced as the Sc flux was increased to 4 nA, where the Sc contents measured by XPS are 0.31, 0.27 and 0.21 respectively. This is likely due to the differences in surface polarity expected to occur between III-nitride films grown by MBE (normally N-polar) and MOVPE (normally Ga-polar) [49,50], as well as differences in the film strain which are well known to affect the relative incorporation of alloy constituents having different ionic radii [51,52] and which may also affect the relative surface accumulation.…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory systems have improved significantly in recent years, becoming easier to operate and equipped with more functional optics and detectors. For example, the availability of high-flux, high-resolution monochromators on laboratory four-circle diffractometers has made specular x-ray scattering and reciprocal space mapping workhorses for determining composition and strain in compound semiconductor systems [Pereira et al 2002]. New advances in x-ray optics [Kang et al 2006] hold forth the promise of focusing hard x-rays down to the nanometer level, opening up a range of scattering and fluorescence methods for application at high spatial resolutions.…”
Section: Potential Research Approachesmentioning
confidence: 99%